Letter : Spanish Republican House - Hogar Español; Evans, Lincoln
001-0083-001 Telegraphic address: bisakta.kincros.London. TELEPHONE TERMINUS 6691.6692,(2 lines) The Iron and Steel Trades Confederation. HEAD OFFICE: Swinton House, 324 Gray's Inn Road, London W.C.1 YOUR REF. OUR REF. CON/LE/NB 28th February 1945 Rt. Hon. Sir Walter Citrine, KBE General Secretary, Trades Union Congress, Transport House, Smith Square, Dear Sir Walter, re Spanish Republican House. I am enclosing a copy of an appeal that was before our Executive Council last week. While they were quite disposed to make some donation in response to this appeal, they were not quite satisfied as to whether it was a bona fide one, and they were wondering whether you have received a similar appeal, and whether such has been considered by your General Council. Any information you can give me with regard to the people making the appeal will be very useful. Yours faithfully Assistant General Secretary. Encl. Copy letter. 292/946/1/83